The Transformation and Utilization of Non-material Resources by First-Generation College Students - Kang, Chengye (International Journal of Social Sciences and Public Administration, 2024)
The growth issues of first-generation college students have always been a focus of attention. This study delves into the subtle interactions and relationships that underlie the non-material resources, encompassing moral emotions and other intrinsic elements associated with the self, which are predicated upon material capital. Through the interpretation of the significance of case study and textual analysis method, we have uncovered the value of immaterial resources as “potential” in some sense, manifesting as an integration of the values of multi-dimensional interconnection and self-subjectivity. The study outlines actionable strategies to help first-generation college students utilize non-material resources across three distinct dimensions: family communication, cultural reinvestment, and self-regenerative capacity.